2020
DOI: 10.3389/fmicb.2020.00418
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Immunogenic Protein Diversity of Erysipelothrix rhusiopathiae Isolated From Pigs in Great Britain: Implications for Vaccine Protection

Abstract: Frontiers in Microbiology | www.frontiersin.org March 2020 | Volume 11 | Article 418 Forde et al. Genomic Diversity of Erysipelothrix rhusiopathiaecommonplace for this bacterium. We hypothesize that the sequence variants in these proteins could be responsible for differences in the efficacy of the immune response. Our results provide the necessary basis for testing this hypothesis through in vitro and in vivo studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 59 publications
2
24
0
4
Order By: Relevance
“…Strain 2-related isolates whereas SpaA and SpaB were found in E. rhusiopathiae (Fig. 1 B), as expected 25 , 34 . No Spa sequence was detected in E. larvae but surprisingly, a Spa protein sequence was found in E. tonsillarum (Supplementary Fig.…”
Section: Resultssupporting
confidence: 74%
“…Strain 2-related isolates whereas SpaA and SpaB were found in E. rhusiopathiae (Fig. 1 B), as expected 25 , 34 . No Spa sequence was detected in E. larvae but surprisingly, a Spa protein sequence was found in E. tonsillarum (Supplementary Fig.…”
Section: Resultssupporting
confidence: 74%
“…One explanation for varying levels of IgY titers to ER between flocks may for instance be that it reflects qualitative variations in the specificity of antibodies due to differences in the ‘flock ER profile’. A large genetic variation among ER strains has been shown [ 22 , 30 ] including in genes of putative importance for immune recognition [ 31 ] and by whole genome sequencing of a large number of ER strains isolated from laying hens during outbreaks of erysipelas we have found that the genetic profile of ER is clearly associated with the farm (manuscript in preparation). Thus, the variation between flocks in levels of ER antibodies when testing with one ER strain may reflect variations in cross-reactivity of antibodies raised to different ER strains than that used to detect the antibodies.…”
Section: Discussionmentioning
confidence: 87%
“…Meanwhile, the number of Acinetobacter strains resistant to multiple antibiotics has increased significantly in recent years, suggesting potential biosafety risks [ 48 ]. Erysipelothrix is extensively distributed in the environment and may survive for a long period [ 49 , 50 ]. Erysipelothrix is a pathogen associated with many occupational diseases, and its pathogenesis may be related to hyaluronidase and neuraminidase produced by bacteria [ 19 ].…”
Section: Discussionmentioning
confidence: 99%